Company Performance with Balance Score Card, Based on Organizational Commitment Through Good Corporate Governance Application - I Nengah Budiarta (Universitas Pendidikan Nasional, 2018)
ABSTRACTEducational business in tourism sector growth so significant in Bali nowadays as the impact of the globalization and Asean Market Open. The research problem are to measure weather balance scorecard, organizing commitment and GCG Application direct or indirect had influenced to company performance or not? The objectives of this research are to measure the impact of balance scorecard, organizing commitment and GCG Application direct or indirect to company performance.The research take place at Monarch Hotel and Cruises Line in Gianyar-Bali. Total sample are 65 staffs, It is used questioner, interview and observation techniques for data collection. Data analysis techniques used SEM (Structural Equation Model) with Partial Least Squares (PLS) software. The result of the studies mention that GCG Application has direct influenced 0,275 to company performance. Balance scorecard, has direct influenced 0,273 to GCG application. Organizing commitment has direct influenced to 0,434 to Company performance. Organizing commitment has direct influenced 0,741 to GCG Application, Balance Scorecard has direct influenced 0,234 to Company Performance.